Preliminary investigation and application of a modified objects memory test in perioperative cognitive evaluation - Chen, Lanfeng; Gao, Baobin; Yan, Chaoyang; Wang, Zhengzheng; Bi, Yiqing; Chen, Hongfu; Jin, Haojie (Frontiers in Behavioral Neuroscience, 2023)
Objective To investigate the applicability of a modified verbal learning test redesigned from the memory subtest of the Syndrom Kurztest (SKT) in perioperative cognitive evaluation. Methods Patients receiving elective herniorrhaphy and their accompanying dependents (set as normal controls), 55-75 years old, were randomly divided into two groups. The two groups received the modified verbal learning test (M-SKT) or a traditional auditory verbal learning test (AVLT). The cognitive evaluation was administered at the bedside on the day before surgery and the second day after surgery. Results The M-SKT test was administered to 121 subjects, while 107 patients received the AVLT test. After confirming that there was no significant difference in cognitive function between patients and their families, the results of the M-SKT and AVLT tests were compared. The results showed that the "low-score" ratio of the M-SKT was significantly lower than that of the AVLT test (P < 0.05), and the influencing factors of the M-SKT were less than those of the AVLT test. However, the learning effect of the M-SKT was more significant (P < 0.05). Conclusion This study preliminarily confirms that the M-SKT has better applicability to elderly Chinese individuals than AVLT in perioperative cognitive evaluation, but its learning effect should be noted.